Prosthesis satisfaction in lower limb amputees: A systematic review of associated factors and questionnaires - Baars, Erwin C. (Medicine (Baltimore), 2018)
BACKGROUND: Factors influencing patient satisfaction with a transtibial prosthesis have been studied fragmentarily. The aims of this systematic review were to review the literature regarding factors of influence on patient satisfaction with a transtibial prosthesis, to report satisfaction scores, to present an overview of questionnaires used to assess satisfaction and examine how these questionnaires operationalize satisfaction. METHODS: A literature search was performed in PubMed, Embase, PsycInfo, CINAHL, Cochrane, and Web of Knowledge databases up to February 2018 to identify relevant studies. RESULTS: Twelve of 1832 studies met the inclusion criteria. Sample sizes ranged from 14 to 581 participants, mean age ranged from 18 to 70 years, and time since amputation ranged from 3 to 39 years. Seven questionnaires assessed different aspects of satisfaction. Patient satisfaction was influenced by appearance, properties, fit, and use of the prosthesis, as well as aspects of the residual limb. These influencing factors were not relevant for all amputee patients and were related to gender, etiology, liner use, and level of amputation. No single factor was found to significantly influence satisfaction or dissatisfaction. Significant associations were found between satisfaction and gender, etiology, liner use, and level of amputation. CONCLUSION: Relevance of certain factors for satisfaction was related to specific amputee patient groups. Questionnaires assessing satisfaction use different operationalizations, making comparisons between studies difficult.